Tebentafusp induces a T-cell-driven rash in melanocyte-bearing skin as an adverse event consistent with the mechanism of action - Hassel, Jessica C.; Stanhope, Sarah; Greenshields-Watson, Alexander; Machiraju, Devayani; Enk, Alexander; Holland, Christopher; Abdullah, Shaad E.; Benlahrech, Adel; Orloff, Marlana; Nathan, Paul; Piperno-Neumann, Sophie; Staeger, Ramon; et al. (The journal of investigative dermatology, 2025)
Tebentafusp is a gp100xCD3-bispecific ImmTAC designed to redirect polyclonal T cells against cells presenting the melanocyte lineage-specific antigen …